사회적지원이 자기효능감, 정서적 고갈 및 조직침묵에 미치는 영향 : 항공사 객실승무원을 대상으로 - 이원화(Won-Hwa Lee); 박정민(Jung-Min Park) (한국콘텐츠학회 논문지, 23(12), 2023)
본 연구는 항공사 객실승무원을 대상으로 사회적지원과 자기 효능감, 정서적 고갈 및 조직침묵간의 관계를 파악해 보고자 국내 항공사 승무원을 대상으로 조사하였고 311부를 최종 분석에 활용하였다. 자료는 데이터 코딩을 거쳐 SPSS 27.0을 활용하여 빈도분석, 신뢰도분석, 탐색적 요인분석, 상관분석을 실시하였고, Amos 27.0을 이용하여 확인적 요인분석과 구조방정식 모형분석을 실시하였다. 실증연구 결과로는 첫째, 사회적지원 중 상사지원과 조직지원은 자기효능감에 정의 영향을 준다. 둘째, 사회적지원 중 상사지원은 정서적 고갈에 유의한 부의 영향을 준다. 셋째, 사회적지원 중 상사지원과 조직지원은 조직침묵에 유의한 부의 영향을 준다. 넷째, 자기효능감은 조직침묵에 영향관계가 확인되지 않았다. 다섯째, 정서적 고갈은 조직침묵에 정의 영향을 준다. 이에 대한 연구의 시사점과 한계점 및 향후 연구방향을 제시하였다. This study conducted an empirical analysis on flight attendants to understand the relationship between the social support, self confidence, emotional depletion, and organizational silence. Of the 327 copies collected through the survey, 311 copies, excluding unfaithful responses and unwritten questionnaires, were used for the final analysis. The data analysis method used SPSS 27.0 to conduct frequency analysis, reliability analysis, exploratory factor analysis, and correlation analysis, and confirmed factor analysis and structural equation model analysis using Amos 27.0. As a result of the empirical study, First, among social support, supervisor support and organizational support have a positive effect on self-efficacy. Second, among social support, supervisor support has a significant negative effect on emotional depletion. Third, among social support, supervisor support and organizational support have a significant negative effect on organizational silence. Fourth, self confidence has not been confirmed to have an influence on organizational silence. Fifth, emotional depletion has a positive effect on organizational silence. The implications and limitations of the study and future research directions were presented. KCI Citation Count: 0